1985
DOI: 10.1128/mcb.5.10.2764
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of sea urchin H2B histone gene transcription by a chromatin-associated protein fraction depends on gene sequences downstream of the transcription start site.

Abstract: We isolated a chromosomal protein fraction derived from chromatin of sea urchin embryos which specifically stimulated the expression of the histone H2B gene by a factor of 5-to 10-fold when the complete sea urchin histone gene repeat h22 was injected in Xenopus laevis oocyte nuclei. Gene manipulation experiments revealed the existence of two different target sites in the H2B gene which appear to mediate the response to injection of the stimulatory sea urchin chromatin-associated proteins; both are located down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Microinjection into oocytes or fertilized eggs of the african clawed toad Xenopus laevis has long been used to study transcription processes (Mous et al, 1985;Gurdon and Wakefield, 1986 and references therein). In the oocyte, there is generally high transcriptional activity, which attenuates as genes are inactivated upon maturation towards the egg.…”
Section: Introductionmentioning
confidence: 99%
“…Microinjection into oocytes or fertilized eggs of the african clawed toad Xenopus laevis has long been used to study transcription processes (Mous et al, 1985;Gurdon and Wakefield, 1986 and references therein). In the oocyte, there is generally high transcriptional activity, which attenuates as genes are inactivated upon maturation towards the egg.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of genes, including histone genes, are accurately transcribed after microinjection into oocyte nuclei, and the injection of genes with mutated promoter regions has enabled the identification of elements required for transcription in the oocyte (16). The Xenopus oocyte system has also been used to identify a trans-acting factor involved in the processing of sea urchin histone mRNAs (34) and, more recently, to identify a factor capable of stimulating sea urchin early H2b gene transcription (30).…”
mentioning
confidence: 99%
“…The TflIIA factor binds with a fourfold-higher affinity to the somatic gene subfamily than to the oocyte gene subfamily. This difference in affinity, together with a decline in the intranuclear concentration of TflIIA during development, has been proposed as an explanation for the inactivation of the oocyte 5S genes in latestage embryos (5,37 Mous et al (30) showed that a 0.3 M salt extract of sea urchin (Psammechinus miliaris) chromatin stimulates expression of early H2b histone genes in Xenopus oocytes. (Late histone genes were not tested.)…”
mentioning
confidence: 99%
“…The discovery of viral enhancer sequences (for a brief review, see reference 18) demonstrated that regulatory elements may also function outside of the more traditionally defined promoter region. It was subsequently demonstrated that a number of cellular genes (including those encoding immunoglobulin heavy and light chains [2,3,11,[28][29][30], human growth hormone [37], and sea urchin H2B [26]) possess internal regulatory elements. Several years ago we set out to investigate the existence of control elements internal to or downstream of goat p-globin genes.…”
mentioning
confidence: 99%